Economic Growth of a Rapidly Developing Economy: Theoretical Formulation - Sukharev, Oleg Sergeyevich (Economy of Regions, 2016)
The subject matter of the article is the description of economic growth. Modern economy is characterized by a high rate of changes. These changes are the limiting parameters of modern development, which requires a modification of the basic models of growth, the substantiation of the expediency and necessity of a rapid development strategy. In a simple mathematical form, the statement of the problem of economic growth in the “green economy” is examined, in which the costs of environmental measures are not considered a priori as hampering economic development (as it is common for a number of modern neoclassical and neo-Keynesian growth models). The methodological basis of the article are the econometric approach and modelling method. The article has a theoretical character. The main hypothesis supposes that the rapid development strategy cannot make an adequate development strategy under certain conditions, but may be acceptable in other its specific conditions. In this sense, the important growth conditions are the availability of resources, the effectiveness of institutions and the current economic structure, the technological effectiveness of economy, as well as the conditions of technological development (“green economy”) and the path of such development. In the article, on the theoretical level of analysis, the substantiation of the adequacy of the rapid development strategy for an economic system is given, whose goal is to achieve the standard of living of the country-leader. Based on the assumptions introduced, the period for which the rapid development strategy might be implemented and the economic lag of the country might be reduced from the country-leader is determined. The conditions that ensure the impact of innovations on the rate of economic development are summarized. The introduced range of dependencies and relations can be useful for the elaboration of the theory of innovation development and for the formation of a new conceptual framework of the model of economic growth of a rapidly changing economic system (competing at high speeds). Based on the analysis of proposed theoretical models for Russia, the following conclusion is made: the rapid development strategy may be effective only if it combines the stimulation and innovations as well as the classic productions, therefore, recreating the earlier lost sectors of economics. This will help to overcome the technological gap.